Training of employees of police security and escort units in the application of self-defense and detention techniques in typical situations of office activities - Trusova N.K. (Theory and Practice of Physical Culture, 2023)
The results of the study revealed the effectiveness of using the situational method and typical situations of using self-defense and detention techniques for training by police officers escorting criminals. One of the priority areas for the development of the situational use of physical force is the search for effective ways of interaction between employees in order to physically suppress the commission of an act of self-harm by a suspect or accused in a protective fence in the courtroom.